Predicted and measured slant ionospheric electron content - Cabrera, Miguel Angel (2005)
The total electron content (TEC) is used to indicate the ionisation of the ionosphere. TEC is a quantity with concern for telecommunications, detection systems, track, position, flight control and other systems that use transionospheric signals, because the ionospheric layer affects the mentioned signals. In this work, the slant ionospheric electron content (SIEC) was modelled. The proposed method uses ‘auxiliary’ station that is determined over the slant link on terrestrial surface projection. This allows to obtain TEC between two points. Two models were considered, viz.: (i) the international reference ionosphere (IRI) and (ii) Chapman layer with scale height equal to atomic oxygen scale height (CHO). The validity of the TEC calculated by both ionospheric models was checked with SIEC measurements obtained with geosynchronous satellites signals, for Boulder–ATS/6 and Palehua–ATS/6 links considering solstices and equinox, in low, moderate and high solar activity periods. In general, in both links, the deviations between predictions and measurements were lower than 30% for about 10–14 h per day. In general, best model predictions are obtained during daylight hours. The results suggest that additional studies for other links and solar activity are required. r 2005 Elsevier Ltd. All rights reserved. Keywords: Electron content; Ionosphere; Transionospheric; Satellite; Models